THE NEED FOR DEVELOPMENT OF SERVICES IN UZBEKISTAN - Isxakova S. A. (Scholar Express Journals, 2022)
The article emphasizes the importance of increasing the volume of services, optimizing its structural structure in the further development of the service sector, and developed scientifically based proposals and recommendations in this regard
Keywords: postindustrial society; economy; material production sector; services